Towards Simulation of Dislocation-Based Creep Mechanisms: Application to Oxide Dispersion Strengthening Steels. (2015) - Robertson, C.; Poissonnet, S.; Panigrahi, B.K.; Sundar, C.S.
Abstract: This paper presents an experimental study on the micro-creep response of a model Oxide Dispersion Strengthening (ODS) ferritic steel, using high temperature nano-indentation testing. The results are interpreted using a theoretical approach based on different dislocation climb mechanisms, accounting for the present testing conditions: high stress and high dislocation density. This work is regarded as a first step towards implementation of dislocation-based creep mechanisms in advanced dislocation dynamics simulations.